Copper Nanoparticle Mediated ‘Click Glycosylation’ for the Synthesis of Fluorinated Triazole Derivatives - K. Al-Duaij, Omar; Guesmi, Ahlem; B. Hamadi, Naoufel (Letters in Organic Chemistry, 2016)
Background: The synthesis of triazole derivatives is a major interest among synthetic organic chemists. Indeed, triazole derivatives, especially containing fluorine atom, present wide applications in the field of science materials. In this aim, we have developed this work to propose a new route for the synthesis of fluorinated triazole derivatives. Methods: Various acetylenic compounds derived from γ- and δ-lactam on reaction with using γ- and δ-lactam and sodium azide in the presence of 5 mol% of copper nanoparticles in water to offered triazole derivatives. Results: Replacement of CH3CN with H2O as a solvent, for the reaction catalyzed by CuNPs to produce fluorinated triazole, was finished within 1 h in 90% yield. Conclusion: A simple and efficient protocol for the synthesis of 1,2,3-triazole derivatives using 5 % of copper nanoparticles was developed.
Keywords: fluoro 1